Trust of Science as a Public Collective Good. Issue 5 (25th December 2022) - Slater, Matthew H.; Scholfield, Emily R.
Abstract: The COVID-19 pandemic and global climate change crisis remind us that widespread trust in the products of the scientific enterprise is vital to the health and safety of the global community. Insofar as appropriate responses to these (and other) crises require us to trust that enterprise, cultivating a healthier trust relationship between science and the public may be considered as a collective public good. While it might appear that scientists can contribute to this good by taking more initiative to communicate their work to public audiences, we raise a concern about unintended consequences of an individualistic approach to such communication.